CMIP6 near-term and long-term projections of Eurasian winter cooling trend and cold extremes - Xu, Xinping; He, Shengping; Zhou, Botao; Sun, Bo (Environmental Research Letters, 2024)
It is well-known that climate warming increases air temperature and reduces cold extremes in the long-term. But internal variability strongly modulates the variability of temperature at mid- and- high latitudes, for example, causing the remarkable cooling and severe winter weather over Eurasia from the 1990s to the early 2010s. It remains unclear whether the occurrence of Eurasian cooling and cold extremes will be offset by climate warming or stimulated by internal variability in the future. Based on the Sixth phase of the Coupled Model Intercomparison Project multi-model projections for 2015–2100, this study shows that the projected probability of Eurasian cooling trend decreases with increasing greenhouse gas concentration in the long-term (i.e. 2070–2099) from 14.8% under SSP126 to 0.9% under SSP585. In the near-term (i.e. 2021–2050), however, Eurasian cooling occurrences are less influenced by different emission scenarios. Coinciding with deep Arctic warming throughout the troposphere, the projected significant Eurasian cooling exhibits similar pattern and intensity among different scenarios. The similar trend towards tropospheric anticyclone over the Arctic among different scenarios in the near-term promotes the deep Arctic warming-Eurasian cooling trend through transporting warm (cold) air into the Arctic (mid-latitudes). Moreover, winter extreme cold anomalies (i.e. −3.0–−2.0 °C) and extreme cold days (i.e. 4–6 d) over the Eurasian continent are not sensitive to emission scenarios in the near-term. In the long-term, the accelerating climate warming under high-emission scenarios significantly reduces the frequency and intensity of Eurasian cold extremes compared to low-emission scenarios. Therefore, the occurrence of Eurasian cooling trend and cold extremes in the near-term will be dominated by internal influences (e.g. Ural blocking) and will rely more on the internal variability after the mid-century if carbon neutrality goal is achieved. publishedVersion